2020
DOI: 10.1097/bpo.0000000000001573
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Floating Elbow Injuries Are Not as Problematic as They Were Once Thought to Be: A Systematic Review

Abstract: Background: Pediatric ipsilateral supracondylar humerus and forearm fractures (floating elbow), are historically reported to have a high rate of complications, including pediatric acute compartment syndrome (PACS). As a result, treatment paradigms for these types of injuries differ in the urgency, extent of fixation, and type of immobilization than if each fracture were treated in isolation. We aimed to systematically review the literature on pediatric floating elbow injuries and assess the reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 32 publications
2
23
3
Order By: Relevance
“…Moreover, it could be an open or closed injury. The prevalence of open injuries varies from 13-22% and are more in humeral rather than forearm fractures [ 7 , 8 , 11 , 12 ]. In our case, we report a peculiar rotational injury by a semi-automatic washing machine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it could be an open or closed injury. The prevalence of open injuries varies from 13-22% and are more in humeral rather than forearm fractures [ 7 , 8 , 11 , 12 ]. In our case, we report a peculiar rotational injury by a semi-automatic washing machine.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the patient came with an impending compartment due to a delay of more than 12 hours, which also could elevate the compartmental pressure [ 14 ]. Contrary to what was believed about the risk of compartment syndrome, some authors propose that it could be an overestimation and it was likely secondary to other factors rather than being from the pattern of the injury itself [ 12 , 14 , 15 ]. Hence, simultaneous ipsilateral forearm fractures and supracondylar fractures do not increase the latter's own risk of acute compartment syndrome [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…From our analysis, four studies assessed the risk of compartment syndrome in which no cases were identified within either the early or delayed surgery group. Recent evidence supports this finding; a systematic review of 11 studies, Baghdadi et al [ 26 ] found that the rate of compartment syndrome in patients with supracondylar fractures was low, ranging from 0 to 12% in incidence with a frequency-adjusted incidence of 2% [ 26 ]. A retrospective analysis in Yaokreh et al [ 27 ] study of 89 children with delayed surgery of 4.5 days for severe supracondylar fractures found that none of the children had developed compartment syndrome as a complication [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…Several small series have reported the development of compartment syndrome after flexible intramedullary nailing of forearm or tibia fractures. The incidence of compartment syndrome after flexible intramedullary fixation of pediatric forearm fractures ranges from 2-7.5%, [23][24][25] (Figures 2a and 2b) with increased operative time and multiple attempts at reduction considered risk factors. Timing may also be an important factor.…”
Section: Epidemiologymentioning
confidence: 99%